Memahami Pelabelan Gizi dan Perilaku Konsumen di India: Sebuah Tinjauan Ruang Lingkup: Understanding Nutrition Labelling and Consumer Behavior in India: A Scoping Review - Sree, Sruthi; Palanisamy, Bharathi; Sivakumar, Sai Prashanthini (Amerta Nutrition, 2025)
Background: Growing burden of non-communicable diseases is a major public health concern in India, with nearly one in five individuals aged 15-49 overweight or obese. In this context, front of pack food labelling is often proposed to guide consumers towards healthier food choices. Yet, there is limited research on how Indian consumers actually interpret and respond to such labels, leaving a gap in understanding its real-world influence on purchasing decisions. Objectives: To examine nutrition label literacy and its influence on consumer behavior in India. The study aimed to assess label understanding, identify factors to effective use, and explore strategies to enhance label functionality. Methods: Scoping review was conducted adopting the PRISMA-ScR method. Literature published from January 2004 to July 2024 was systematically searched on Scopus, PubMed, and ProQuest databases. Studies were included if they examined knowledge, awareness or implementation of nutrition labelling among Indian consumers. Discussions: 12 of 1256 cited articles were included. Findings showed that barriers to effective label use included inadequate use of detailed information, inclination towards user-friendly format such as warning labels, and pervasive misinformation related to packaged foods. Educational interventions, especially among youth, had the potential to enhance label literacy. While FSSAI has made regulatory progress, the voluntary and inconsistent Front-of-Pack (FoP) labelling remains insufficient. Conclusions: Nutrition labelling in India has not reached its full effect. Mandatory warning labelling, standardized packaging, school-based education, and active regulatory action are proposed. Stepwise, multi-sectoral action is the key to labelling of food products becoming a stronger public health intervention.